KONSELING PEREMPUAN - Ulfiah Ulfiah (Psympathic : Jurnal Ilmiah Psikologi, 2010)
Women have the same status as the man. There is no differences of status and human right between women and men. Both men and women have the same function in the social life. In the long history, women had the important role. With their achievement, Islam has given the large area to the women in doing good action and heroic. Islam has shown a good position for the women in social life. In the global area, the role of women and men had changed. Women tends to get the public role. The tendencies of women change is because of the opened opportunities for the women. This Phenomenon gives the opportunities to the women to express their  potential. But it will be  a problem if the women don’t understand the role of gender totally. So, counseling has to give the right understanding  in expressing their potential.